2000
DOI: 10.1007/s004040050282
|View full text |Cite
|
Sign up to set email alerts
|

Sexual assault under benzodiazepine submission in a Paris suburb

Abstract: Sexual assaults under benzodiazepine submission have been described, since use of benzodiazepine enables non consensual sexual activity but rarely fully reported. An accurate evaluation of the phenomenon has seemed interesting. Files of 23 adult males and females examined at the Emergency Forensic Unit of an University Teaching Hospital near Paris were reviewed. All the victims had complained from sexual assault under drug submission, in the years 1996 and 1997. A complete examination for sexual assault was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 10 publications
1
15
1
Order By: Relevance
“…The rate of suspected drugging in this study was higher than that reported in chart reviews of cases of sexual assault from similar specialized services in Victoria, Australia (17.5%), 7 Vancouver, Canada (12.1%), 1 Paris, France (6.3%), 8 and Minneapolis, United States (7.0%). 9 This difference may be related to the systematic and prospective collection of data in our study, our definition of drug-facilitated sexual assault and the year of our study.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…The rate of suspected drugging in this study was higher than that reported in chart reviews of cases of sexual assault from similar specialized services in Victoria, Australia (17.5%), 7 Vancouver, Canada (12.1%), 1 Paris, France (6.3%), 8 and Minneapolis, United States (7.0%). 9 This difference may be related to the systematic and prospective collection of data in our study, our definition of drug-facilitated sexual assault and the year of our study.…”
Section: Discussioncontrasting
confidence: 46%
“…1,[7][8][9] One such study demonstrated that the incidence of hospital-reported drug-facilitated sexual assault had shown a marked and continuing increase since 1999.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These features are important in order to avoid accidental poisoning by children for example (McIntire et al, 1976). Nevertheless, these preventive processes (including coloration of the solution), can not absolutely prevent the adjunction of the liquid solution in a glass of water, a process described in case reports of chemical submission (Marc et al, 2000;Bismuth et al, 1997).…”
Section: Discussionmentioning
confidence: 97%
“…benzodiazepin-2-one, flunitrazepam) (I) has received a great deal of attention due its medical [1] and increased elicit usage [2][3][4][5][6][7]. It produces a variety of actions, including sedative effects, anxiolytic muscle-relaxation with a pronounced hypnotic effect and memory loss [8].…”
mentioning
confidence: 99%